Crystal structure of the intermetallic compound SrCdPt - Fakhili Gulo; Jürgen Köhler (Acta Crystallographica Section E, 2014)
The crystal structure of the title compound, strontium cadmium platinum, adopts the TiNiSi structure type with the Sr atoms on the Ti, the Cd atoms on the Ni and the Pt atoms on the Si positions, respectively. The Pt atoms form cadmium-centred tetrahedra that are condensed into a three-dimensional network with channels parallel to the b-axis direction in which the Sr atoms are located. The latter are bonded to each other in the form of six-membered rings with chair conformations. All atoms in the SrCdPt structure are situated on a mirror plane.